Bovine Embryonic Mortality with Special Reference to Mineral Deficiency, Heat Stress and Endocrine Factors: A Review - Kumbhar, Umesh B.; Charpe, Bhushan Kumar; Kumar, Sarbjeet (International Journal of Bio-resource and Stress Management, 2021)
Embryonic Mortality is the major cause of reproductive and economic loss in cattle and Buffaloes. Embryonic Mortality is more common during the early than the late embryonic period, i.e., from day 8th to 16th at the hatching of blastocysts and initiation of elongation and commencement of implantation without affecting cycle lengths. Early embryonic mortality is a major source of embryonic and economic loss with mortality rate up to 40%. Embryonic mortality is also reported due to mineral deficiency and heat stress in cattle and buffaloes. Physical modifications of animal environment, nutritional management with Antioxidant, trace minerals and genetic development of breeds that are less sensitive to heat stress should be best solution. Embryonic death occurs at the time of maternal recognition of pregnancy, probably related to a failure of the Interferon tau (IFNι) secretory mechanism along with progesterone deficiency and luteal insufficiency. Recent research, both in terms of physiological mechanisms and pharmacological treatments has mostly focused on the period of maternal recognition of pregnancy or the anti-luteolytic effect. hCG/ GnRH /Progesterone supplementation have shown positive results. Supplementation of interferon as anti-luteolytic agent and supplementing Omega-3 has shown encouraging results. Ovarian examination, Animal history, blood/milk progesterone levels, PAG test and ultrasound appear to be the only practical tool presently available for diagnosis of embryonic mortality. This present review article is covering all the aspects of embryonic mortality with special reference totrace minerals, heat stress, hormonal impact and interferon tau.